Proceedings of the Workshop in Primary and Secondary Computing Education 2015
DOI: 10.1145/2818314.2818340
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Computer Science to 5-7 year-olds

Abstract: Changes to school curriculums increasingly require the introduction of computer science concepts to younger children. This practical report compares three existing tools for teaching computer science concepts: unplugged computing, tangible computing and MIT's Scratch. We specifically focus on the use of these tools for school pupils aged 5-7. We describe a comparative study with 28 pupils from three rural UK primary schools that explores engagement with, and effectiveness of, each tool. As far as we are aware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…With the rising prevalence of CT initiatives and curricula, there has also been an increase in research on CT in education, especially after Wing's (2006 [1]) seminal article proposing CT as a critical foundational academic skill. Since then, various studies have set out to define CT and its effective implementation in education.…”
Section: Recent International Research On Ct In Early Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rising prevalence of CT initiatives and curricula, there has also been an increase in research on CT in education, especially after Wing's (2006 [1]) seminal article proposing CT as a critical foundational academic skill. Since then, various studies have set out to define CT and its effective implementation in education.…”
Section: Recent International Research On Ct In Early Educationmentioning
confidence: 99%
“…Relevant answers to these questions relate to a process called Computational Thinking (hereafter, CT). Along with being crucial to coding and computer science in general, CT is an important skill set across many academic and professional domains (Wing, 2006 [1]) (Wing, 2011[2]) (Bers, 2021[3]). CT, which fosters analytical problem solving along with creative expression, is the driving force behind new initiatives focused on introducing young children to programming (Bers, 2021[3]).…”
Section: Introductionmentioning
confidence: 99%
“… Embodied interaction promotes the understanding of computational thinking Related studies have shown that children aged 5–7 years old appear to have many problems understanding the programming environment itself when directly confronted with Scratch programming but have a higher level of understanding of concepts related to programming during computational thinking game interaction activities [66]. This embodied meaningful representation preserves the concept's core content and offloads the cognitive load to some extent, reducing the difficulty of understanding the concept.…”
Section: A Teaching Practice Framework To Support the Development Of ...mentioning
confidence: 99%
“…Many empirical studies have shown that these programming tools are adequate for developing computational thinking [3,23,50,66]. In recent years, with the development of computer science education, code, graphical, hybrid, and unplugged forms of programming have been widely used in K-12 to develop learners' computational thinking [28,53,58,63].…”
mentioning
confidence: 99%
“…Besides, in the process of combining the two single programming approaches, there is still a lack of systematic research on whether the order of the two programming teaching approaches will affect the teaching effect. In addition, considering the imbalance of education and economic development in different regions, many junior high schoolers are still not able to operate and use computers proficiently, and even schools do not have the conditions to configure computers (Wohl et al., 2015). However, there is currently a lack of representative cases of unplugged activities in junior high school.…”
mentioning
confidence: 99%